Rubber rope exercises and their impact on the accuracy of archery among the female players of the national team for bow and arrow in the arab championship - Mohamed, A. A. Q. A. (Iraqi Journal of Humanitarian, Social and Scientific Research, 2023)
Archery is one of the games that depend on the scoring level of achievement, and we rarely find it has its own measure compared to other sports. The research sample consisted of (60) young archers who participated in the Asian Cup which was held in the city of Sulaymaniyah. The study reached the following results